2013
DOI: 10.1155/2013/892065
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor-Loaded Biomaterials for Mesenchymal Stem Cell Recruitment

Abstract: Human adult mesenchymal stem cells (MSC) can be readily harvested from bone marrow through aspiration. MSC are involved in tissue regeneration and repair, particularly in wound healing. Due to their high self-renewal capacity and excellent differentiation potential in vitro, MSC are ideally suited for regenerative medicine. The complex interactions of MSC with their environment and their influence on the molecular and functional levels are widely studied but not completely understood. MSC secrete, for example,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Another growth factor involved in MSC migration is hepatocyte growth factor (HGF), which binds to c-met [63,68,80] . Both PDGF-BB and HGF have been loaded on gels or scaffolds as a means to improve the in vitro migration of MSCs [92,93] .…”
Section: Marrow) Homingmentioning
confidence: 99%
“…Another growth factor involved in MSC migration is hepatocyte growth factor (HGF), which binds to c-met [63,68,80] . Both PDGF-BB and HGF have been loaded on gels or scaffolds as a means to improve the in vitro migration of MSCs [92,93] .…”
Section: Marrow) Homingmentioning
confidence: 99%
“…Several studies [11][12][13] have reported that HGF induced MSCs to differentiate into hepatocytes in vitro and promotes MSCs in the liver in vivo. Therefore, MSCs combined with HGF gene modification may be a better strategy for the treatment of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Then a longer release from fibroblasts takes place [22]. HGF is a potent chemoattractant for mesenchymal stem cells [23] and has been also shown to be a powerful regulator of proteolytic enzymes involved in extracellular matrix remodeling [22]. A study on skin wound healing has provided evidence that HGF can accelerate reepithelialization by transforming epidermal cells through dedifferentiation to stemlike cells, with powerful ability of proliferation and migration [24].…”
Section: Discussionmentioning
confidence: 99%